O jornalista em ambiente multiplataforma: desafios profissionais na era do jornalismo pós-industrial - Brasileiro, Amy Nascimento (2021)
This research aims to understand the reformulation of the identity of the journalist before the reality of post-industrial journalism. In a context of reconfigurations in the production, consumption, and distribution of news, fostered through the insertion of disruptive technologies in daily life. Our goal is to understand the current work scenario of journalism in the contemporary world and how professionals have experienced such transformations and acted to ensure their space in the job market. To do so, we analyzed the production routine in the integrated newsroom of TV Borborema, in Campina Grande, with empirical purpose being the journalists who work in the production of multiplatform content. We use non-participant observation, with the application of a questionnaire and semi-structured interview, aimed at professionals on TV Borborema. Through an exploratory character, the case study aims to understand the dimensions of the professional profile of a journalist within a context of work in media. The results obtained point to the existence of a multipurpose professional, who experiences several tensions related to the new forms of news production and tries to adapt to technological innovations in view of the precariousness of work relationships in communication institutions.